Repositioning UK Partnerships Post-Brexit - Highman, Ludovic (International Higher Education, 2018)
On such divisive issues as EU membership and, consequently, the post-Brexit relationship between the United Kingdom and the European Union, it is unsurprising that Theresa May’s government has been torn between a “hard” and a “soft” Brexit. As of June 2018, there is still no indication of which approach will prevail, putting at risk UK universities’ participation in the Erasmus+ program, which has provided, among other things, opportunities for over four million Europeans to study, train, and volunteer abroad since its inception. Full access to EU research funds is also at risk. Universities cannot depend on the UK government’s help in securing the frameworks allowing for continuity. In such a context, universities have started to use their limited resources to secure bilateral international and European links to foster research collaboration and staff and student mobility, post-Brexit.